Nietzsche and The birth of tragedy - Daniels, Paul Raimond; Cambridge eBooks (Durham : Acumen Publishing, 2013)
Nietzsche's philosophy is both revolutionary and profound, reaching into all spheres of the arts. The acuity of his ideas and the complexity of his writings ensure Nietzsche's enduring power to engage his readers. Nietzsche's first book, The Birth of Tragedy, is an astonishing analysis of the meaning of Greek tragedy. He confronts us with the idea that the grave truth of our existence can be revealed through tragic art, and that our relationship to the world can be transfigured from pessimistic despair into sublime elation and affirmation. Nietzsche and The Birth of Tragedy provides a clear account of the text and its philosophical, literary and historical influences. Each chapter examines part of the text, explaining the ideas presented and assessing relevant scholarly points of interpretation. The book will be an invaluable guide to readers in philosophy, literary studies and classics coming to The Birth of Tragedy for the first time.
Nietzsche and the influences on The Birth of Tragedy -- Apollo and Dionysos in dialectic (1-6) -- The tragic moment (7-10) -- The decline and death of Greek tragedy (11-15) -- Modernity and the rebirth of tragedy (16-25) -- Appraising The Birth of Tragedy: Nietzsche in his later writings.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Electronic books